Do the Lifestyle and Socio-Economic Status of Students' Parents Affect Students' Consumption Behavior? An empirical study on Satya Wiyata Mandala University Students - Dian Anugrah Sanusi; Letarius Tunjanan; Detty Sajow (Department of Business and Entrepreneurship, Faculty of Economics and Business, Universitas Negeri Makassar, 2023)
The purpose of this study is to examine how Satya Wiyata Mandala University students' consumption patterns are influenced by their lifestyle choices and their parents' socioeconomic standing. This study employs a survey research design and a quantitative methodology. The sample in this study consisted of 197 students, whereas the population consisted of all Satya Wiyata Mandala University students. The method used to collect data is the distribution of questionnaires. With the aid of the SPSS 21 program, statistical analysis is used in the data analysis approach. The study's findings indicate that parents' socioeconomic level and lifestyle choices have an impact on pupils' consumption habits. This study's conclusion is that while examining students' consumption patterns, lifestyle variables and parents' socioeconomic level should be taken into consideration.